Functional analysis of two PLA2G2A variants associated with secretory phospholipase A2-IIA levels. - Holly J Exeter; Lasse Folkersen; Jutta Palmen; Anders Franco-Cereceda; Jackie A Cooper; Anastasia Z Kalea; Ferdinand Van't Hooft; Per Eriksson; Steve E Humphries; Philippa J Talmud (PLoS ONE)
Background Secretory phospholipase A2 group IIA (sPLA2-IIA) has been identified as a biomarker of atherosclerosis in observational and animal studies. The protein is encoded by the PLA2G2A gene and the aim of this study was to test the functionality of two PLA2G2A non-coding SNPs, rs11573156 C>G and rs3767221 T>G where the rare alleles have been previously associated with higher and lower sPLA2-IIA levels respectively. Methodology/principal findings Luciferase assays, electrophoretic mobility shift assays (EMSA), and RNA expression by RT-PCR were used to examine allelic differences. For rs3767221 the G allele showed ∼55% lower luciferase activity compared to the T allele (T = 62.1 (95% CI 59.1 to 65.1) G = 27.8 (95% CI 25.0 to 30.6), p = 1.22×10⁻³⁵, and stronger EMSA binding of a nuclear protein compared to the T-allele. For rs11573156 C >G there were no luciferase or EMSA allelic differences seen. In lymphocyte cell RNA, from individuals of known rs11573156 genotype, there was no allelic RNA expression difference for exons 5 and 6, but G allele carriers (n = 7) showed a trend to lower exon 1-2 expression compared to CC individuals. To take this further, in the ASAP study (n = 223), an rs11573156 proxy (r² = 0.91) showed ∼25% higher liver expression of PLA2G2A (1.67×10⁻¹⁷) associated with the G allele. However, considering exon specific expression, the association was greatly reduced for exon 2 (4.5×10⁻⁵) compared to exons 3-6 (10⁻¹⁰ to 10⁻²⁰), suggesting rs11573156 G allele-specific exon 2 skipping. Conclusion Both SNPs are functional and provide useful tools for Mendelian Randomisation to determine whether the relationship between sPLA2-IIA and coronary heart disease is causal.